Rituximab With or Without a Conventional Maintenance Agent in the Treatment of Relapsing Granulomatosis With Polyangiitis (Wegener's): A Retrospective Single‐Center Study. Issue 10 (October 2014) - Azar, Lama; Springer, Jason; Langford, Carol A.; Hoffman, Gary S.
<x xml:space="preserve">Abstract</x> Objective To evaluate the efficacy and safety of rituximab (RTX) induction therapy and the duration of remission, when RTX is used with or without a conventional maintenance agent, in a cohort of patients with granulomatosis with polyangiitis (Wegener's) (GPA). Methods This was a retrospective, single‐center study of patients with relapsing GPA treated with at least 1 course of RTX (4 weekly doses of 375 mg/m2 intravenously [IV] or 2 fixed doses of 1, 000 mg IV 2 weeks apart). Complete remission was defined as the absence of disease activity measured by a Birmingham Vasculitis Activity Score for Wegener's granulomatosis of 0 and not qualified by the prednisone dosage at the time. Results Eighty‐nine patients achieved remission after their first course of RTX and were not re‐treated preemptively with RTX to maintain remission of their disease during followup. Among these patients, relapse‐free survival was significantly higher in those who received a conventional maintenance agent (azathioprine, methotrexate, or mycophenolate mofetil) in conjunction with RTX and glucocorticoids (n = 47) than in those who received no additional immunosuppressive agent (n = 42) (P = 0.04). The hazard ratio of relapse in those receiving a maintenance agent was 0.53 (95% confidence interval 0.29–0.97). Serious adverse events did not differ between the 2 groups. Within a subset of 15 patients in the cohort who were relapse free 2 years after 1 course of RTX, remissions endured for 2–6 years in 8 patients. Conclusion RTX is an effective remission‐inducing agent in GPA. The addition of a conventional maintenance agent to RTX and glucocorticoids decreased the incidence of relapse and did not result in a higher incidence of adverse events.